Determining the effect of tung biodiesel on thermodynamic, thermoeconomic, and exergoeconomic analyses at high engine speeds - Şanlı, Bengi; Güven, Onur; Özcanlı, Mustafa; Uludamar, Erinç (Frontiers in Energy Research, 2024)
Tung biodiesel is a promising alternative fuel type produced from the tung tree. In the current study, the effect of 20% by volume addition of tung biodiesel to diesel fuel was evaluated in terms of energetic-exergetic analyses based on first and second laws of thermodynamic at various high engine speeds (2400 rpm, 2600 rpm, and 2800 rpm). Additionally, this study aims to assess thermoeconomic and exergoeconomic aspects of the diesel engine. The findings revealed that the amount of energy converted to the useful work for the diesel fuel was higher than DTB20 fuel, even though the fuel energy obtained from DTB20 fuel was higher than that of diesel fuel at all engine speeds. The highest energy and exergy efficiencies for the engine fueled with diesel fuel were obtained as 35.95% and 33.73%, respectively while the corresponding values for the engine fueled with DTB20 fuel were determined as 34.97% and 32.58% at the engine speed of 2600 rpm. However, at 2800 rpm, a significant decrease in both energy and exergy efficiencies was observed for both diesel and tung biodiesel blended fuel due to increased mechanical friction of the engine components. Furthermore, at the highest engine speed, entropy generation increased owing to a higher exergy destruction rate. The entropy generation increased to 0.38 kW/K for diesel fuel and 0.46 kW/K for DTB20 fuel since the enhancement of the engine speed caused to the ascend of fuel consumption rate. Regarding thermoeconomic-exergoeconomic analyses, for both diesel and tung biodiesel blended fuels, there is no distinct difference in thermoeconomic-exergoeconomic parameters at 2400 rpm and 2600 rpm as the values of these parameters at the engine speed of 2800 rpm increased significantly. In the light of all findings, it can be concluded that the engine speed of 2800 rpm is not applicable to run the engine due to higher friction and correspondingly energy destruction in the engine system.